2020
DOI: 10.1002/cpt.2104
|View full text |Cite
|
Sign up to set email alerts
|

Model‐Informed Drug Development for Antimicrobials: Translational PK and PK/PD Modeling to Predict an Efficacious Human Dose for Apramycin

Abstract: Conflict of Interest SNH is a co-founder of Juvabis AG, a startup biotech company with an interest in aminoglycoside therapeutics. All other authors declared no competing interests for this work. Funding Some of the research leading to these results was conducted as part of the ND4BB European Gram-Negative Antibacterial Engine (ENABLE) Consortium (www.nd4bb-enable.eu) and has received funding from the Innovative Medicines Initiative Joint Undertaking under grant agreement n°115583, resources of which are compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 43 publications
6
44
0
Order By: Relevance
“…Apramycin, which is in Phase I clinical trials, has been shown to be active against Enterobacterales that produce 16S-RMTases, which confer resistance to all other currently available aminoglycosides. 116 , 117 Although limited data about apramycin against MBL-producing Enterobacterales is currently available, it holds potential to become a therapeutic option for MBL-producing Enterobacterales based on its spectrum of activity.…”
Section: Introductionmentioning
confidence: 99%
“…Apramycin, which is in Phase I clinical trials, has been shown to be active against Enterobacterales that produce 16S-RMTases, which confer resistance to all other currently available aminoglycosides. 116 , 117 Although limited data about apramycin against MBL-producing Enterobacterales is currently available, it holds potential to become a therapeutic option for MBL-producing Enterobacterales based on its spectrum of activity.…”
Section: Introductionmentioning
confidence: 99%
“…In our model, the EBL-1003 exposure in plasma and ELF (fAUC plasma and fAUC ELF , respectively) achieved by doses corresponding to the predicted therapeutic dose for systemic Escherrichia coli infections in humans (30 mg/kg) were considerably higher than the predicted target values for A. baumannii [17]. PK/PD predictions suggested >99•9% PTA for MIC ≤8 µg/mL in the lung of healthy individuals and even higher PTA in patients with a reduced (80 mL/min) creatinine clearance, representative of typical patients in the target patient population [27,28].…”
Section: Pkpd and Probability Of Target Attainment (Pta) Analysismentioning
confidence: 83%
“…The AUC plasma of 339 h×μg/mL for this dose in mice roughly corresponds to the expected therapeutic AUC in humans ( Figure 3B). The human dose predicted to achieve a similar AUC plasma exposure level is approximately 30 mg/kg [17].…”
Section: Lung Efficacy Dose Fractionation Studies Lung Pk and Maldi-mentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these earlier studies, we recently found T > MIC to have a higher correlation than AUC/ MIC in the thigh infection mouse model for the aminoglycoside apramycin, currently in clinical development. 18 Correlations for the two indices were, however, similar when only data from the q2h to q8h intervals were considered. There is consequently a dependence on the PK profile and the dosing interval in relation to the half-life of the drug for the correlations obtained.…”
Section: Limitation Of Static Pk/pd Targets For Translationmentioning
confidence: 85%